Sodobna poezija Beneške Slovenije - Bandelj, David (Jezik in slovstvo, 2016)
The paper tries to show the differences between the concepts of engaged poetry developed by generations of poets in Venetian Slovenia. Due to their different historical and political situations, these poets have developed a very modern model of engaged poetry, connected to their relation to "the Other". This model is of great interest, especially due to the use of a dialectal base.
Keywords: Slovenci v Italiji; slovenska zamejska književnost; slovenska poezija; sodobna poezija; angažirano pesništvo; Beneška Slovenija; Slavia Friulana; 20./21.st.